KONSEKUENSI JOB INSECURITY PADA KARYAWAN ENTRY LEVEL - Pusalia, Retno; Prihatini, Dewi; Priyono, Agus; Ekowati, Dian (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2019)
The existence of job insecurity (JIS) cannot be avoided by every individual, including employees. Competition in the tight working world requires a variety of qualifications that must be fulfilled by every employee, particularly in maintaining their existence in the working world, including entry level employees. As the lowest position in the corporate structure hierarchy, entry levels are vulnerable to JIS. This is because entry level at the early stages of career. However, generally, entry level is the spearhead of the company, thus directly or indirectly it will affect performance both individually and a whole of company. The aim of this study is to explain the influence of JIS on employees, particularly entry level. The census method was used in this study. The results of the study shows that JIS has a significant negatif effect on work performance and organizational commitment. Besides that the results also shows that there is no significant influence between JIS on satisfaction and intention to quit the employee. One of the implications of this study is to become a referral for managers, especially in managing JIS in the organization as a whole.